2011
DOI: 10.1177/0897190011407777
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey on Hospital Formulary Management Processes

Abstract: Portions of the ASHP guidelines have been implemented by most institutions, while 35% of institutions have yet to address The Joint Commission's clarification to approve drugs for specific indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In 2011, a survey evaluating formulary Am J Health-Syst Pharm-Vol 71 Mar 1, 2014 management practice revealed that 46 (88%) of the 52 respondents tracked the use of nonformulary medications. 20 However, the authors acknowledged that it was not possible to compare nonformulary medication use among institutions because various metrics were used. The limited data required to create our formulary compliance dashboard (medication name, formulary status, admission number) are readily available and retrievable in most pharmacy information systems and hospitalwide EMRs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, a survey evaluating formulary Am J Health-Syst Pharm-Vol 71 Mar 1, 2014 management practice revealed that 46 (88%) of the 52 respondents tracked the use of nonformulary medications. 20 However, the authors acknowledged that it was not possible to compare nonformulary medication use among institutions because various metrics were used. The limited data required to create our formulary compliance dashboard (medication name, formulary status, admission number) are readily available and retrievable in most pharmacy information systems and hospitalwide EMRs.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is a need to use the presented indicators, assistance in data compilation is needed. Strong leadership and adequate resources may produce more effective P&TC with greater effect on health practices thus leading to improved patient outcomes (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall respondent sample size is similar to that of a previous national survey of institutions' formulary management processes (52 respondents) and provide an important initial perspective on the practice domains assessed in our survey. 25 In addition, respondents were predominantly pharmacists (94.2%), which may be related to the method of identifying health care professionals who likely participate in P&T committee tasks. Despite their majority representation, pharmacists were the health care professionals most often reported to be authors of P&T committee documents; therefore, the training and responsibilities reported could be considered reflective of P&T committee members and contributors who typically provide formulary decision support.…”
Section: Limitationsmentioning
confidence: 99%